The Role of Posyandu Cadres in Improving the Nutritional Knowledge of Under-Five Mothers at Ambacang Padang Health Center - Zaida Maulidiyah; Grace Carol Sipasulta; Urhuhe Dena Siburian (CV. Get Press Indonesia, 2025)
To determine the effectiveness of nutrition education provided by Posyandu cadres in improving the nutritional knowledge of mothers of young children. Methods. The study was conducted in the working area of the Ambacang Community Health Centre, Padang City, West Sumatra, from March to May 2025. A structured questionnaire consisting of demographic data and 20 questions regarding basic knowledge of toddler nutrition (complementary feeding, balanced diet, and toddler feeding frequency) was used to collect data. The results of the paired t-test statistical test showed a significant difference in the average knowledge scores of mothers before and after education (p = 0.000). The univariate analysis in this study showed that most mothers under five had a low level of nutritional knowledge, which was 56%. Conclusions. This study confirms that nutrition education from Posyndu cadre plays a strategic role in improving nutritional literacy of mother of toddlers through a systematic and interactive educational approach. The practical implication of this study is that the results can be used as a basis for community health centres, health offices, and policy makers to strengthen cadre empowerment programmes as the spearhead of community nutrition education.